Delta‐like canonical Notch ligand 3 as a potential therapeutic target in malignancies: A brief overview. Issue 8 (30th June 2021) - Matsuo, Kentaro; Taniguchi, Kohei; Hamamoto, Hiroki; Inomata, Yosuke; Komura, Kazumasa; Tanaka, Tomohito; Lee, Sang‐Woong; Uchiyama, Kazuhisa
Abstract: Delta‐like canonical Notch ligand 3 (DLL3) is a member of the Delta/Serrate/Lag2 (DSL) Notch receptor ligand family and plays a crucial role in Notch signaling, which influences various cellular processes including differentiation, proliferation, survival, and apoptosis. DLL3 is expressed throughout the presomitic mesoderm and is localized to the rostral somatic compartments; mutations in DLL3 induce skeletal abnormalities such as spondylocostal dysostosis. Recently, DLL3 has attracted interest as a novel molecular target due to its high expression in neuroendocrine carcinoma of the lung. Moreover, a DLL3‐targeting Ab‐drug conjugate, rovalpituzumab tesirine (ROVA‐T), has been developed as a new treatment with proven antitumor activity. However, the development of ROVA‐T was suspended because of shorter overall survival compared to topotecan, the second‐line standard treatment. Thus, several studies on the mechanism and function of DLL3 in several malignancies are underway to find a new strategy for targeting DLL3 . In this review, we discuss the roles of DLL3 in various malignancies and the future perspectives of DLL3 ‐related research, especially as a therapeutic target. Abstract : Delta‐like canonical Notch ligand 3 (DLL3) plays a pivotal role in maintaining malignant growth and is related to poor prognosis, especially in relatively rare neuroendocrine subtypes.